Student Sentiment and Academic Achievement in Indonesian Language Learning - Praptanti, Isnaeni; Wahyudi, Wahyudi; Saputra, Wildan Aji; Wiarsih, Cicih; Irianto, Sony (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study examines the relationship between students' perception of Indonesian courses and their impact on academic performance. Through a quasi-experimental design, this study combines quantitative surveys, social media sentiment analysis with big data-based NLP, and statistical regression of academic records from 1,200 students at 10 universities in Indonesia. The study results show that students' negative perception of Indonesian courses has a significant negative correlation with their academic achievement. Through regression and correlation analysis, it was found that students with higher levels of negative sentiment towards this course tended to have a lower Cumulative Grade Point Average (GPA), with R² = 0.23 (p < 0.001) which suggests that the negative perception of the course can explain the variability of a GPA of 23%. These findings suggest that an unpleasant learning experience can significantly affect students' academic performance, especially when associated with teaching methods, curriculum relevance, and students' academic burden. The implications of this study confirm that curriculum reform and technology-based pedagogical innovation are not only needed to improve students' learning experience, but also play a role in optimizing academic outcomes.